Pengaruh Social Media Marketing, Influencer Marketing dan Lokasi terhadap Customer Loyalty Generasi Z pada Kedai Wanus Kedir - Rohmatul Habibah; Aprilia Dian Evasari; Endah Kurnawati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2026)
This study aims to determine the influence of Social Media Marketing, Influencer Marketing, and Location on Generation Z Customer Loyalty at Kedai Wanus Kediri. This research is quantitative. Data were obtained through two methods: primary and secondary data. The population in this study were Generation Z consumers at Kedai Wanus Kediri. The sample in this study was 100 consumers, with accidental sampling as the sampling technique. The analysis techniques used in this study included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results of the partial t-test indicate that the variables Social Media Marketing, Influencer Marketing, and Location have a positive and significant effect on Generation Z Customer Loyalty at Kedai Wanus Kediri. The results of the simultaneous F-test indicate that Social Media Marketing, Influencer Marketing, and Location have a positive and significant effect on Generation Z Customer Loyalty at Kedai Wanus Kediri.